Technical feasibility and impact of balinese cattle marketing toward income of the breeder in badung regency, bali - Ni Made Ayu Gemuh Rasa Astiti; Siti Azizah (Faculty of Animal Science, Universitas Brawijaya, 2019)
The research was conducted from January to June 2018 at the animal market of Beringkit, Badung Regency, Bali. The objectives of the research were to study technical feasibility of Balinese Cattle breeding in Badung Regency, Bali, and the impact of Balinese cattle marketing toward the income of the breeders. The research is explorative research through a survey, which is designed as an explanatory research design. The method of research used a combination of qualitative and quantitative methods. The research was conducted toward the breeders of Balinese cattle on some markets in Badung Regency with 50 respondents of the research who were selected as purposive sampling. Criteria of the respondents include breeders who raise the brood cow. Instruments or tools of the research used the closed and structured questionnaires, which are equipped with open questions. Results of the research showed that technical feasibility of Balinese cattle breeding in Badung Regency, Bali, is considered to be appropriate because the stocks, cattle barn, feeds, and workforce that are utilized for public animal husbandry operation are always managed by the breeders, and the breeders are highly responsible for their cattle. The impact of Balinese Cattle marketing toward the income of the breeders is significant and the tendency of the breeders to sell their cattle when in urgent conditions cause low income for them.